Elevated levels of neuropeptide Y in preeclampsia: A pilot study implicating a role for stress in pathogenesis of the disease. (February 2016) - Paiva, Sara P.C.; Veloso, Clara A.; Campos, Fernanda F.C.; Carneiro, Márcia M.; Tilan, Jason U.; Wang, Hongkun; Umans, Jason G.; Zukowska, Zofia; Kitlinska, Joanna
Abstract: Objective: To determine if preeclampsia (PE) is associated with dysregulation of the neuropeptide Y (NPY) system. Methods: The study enrolled 114 subjects either with normal pregnancy (NP) or with PE. Systolic blood pressure (SBP) was collected from patients using a standard sphygmomanometer. The PE patients were divided into two groups based on the gestational age (GA) at delivery — placental PE (PLPE, GA < 34 weeks) or maternal PE (MTPE, GA ≥ 34 weeks). NPY was measured in platelet rich plasma (PRP), platelet poor plasma (PPP) and in the serum of NP and PE patients utilizing radioimmunoassay. Serum levels of soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF) were measured in NP and PE subjects by ELISA. Results: SBP was higher in PE compared to NP. Circulating NPY in serum and PRP, as well as NPY content per 100, 000 platelets, but not its concentrations in PPP, were elevated in PE, as compared to NP. The highest NPY concentrations were observed in sera and PRP of patients with MTPE. PE patients had also elevated levels of sFlt-1, as compared to NP, although no difference between PLPE and MTPL groups were observed. There was no increase in P1GF in PE patients. Conclusion: Systemic NPY is elevated in PE patients, as compared to NP. This increase is observed in blood fractions containing platelets, suggesting accumulation of the peptide in these cells. NPY concentrations are particularly high in patients with MTPE, underlying differences in etiology between PLPE and MTPE. Our study implicates NPY as a potential target in antihypertensive therapies for PE patients. Highlights: Systemic levels of neuropeptide Y are elevated in patients with preeclampsia. In women with preeclampsia neuropeptide Y accumulates in platelets. Neuropeptide Y concentrations are particularly high in maternal preeclampsia. Neuropeptide Y is a potential target for antihypertensive preeclampsia therapy.